Partisipasi Masyarakat Dalam Pengelolaan Dana Desa di Desa Biluango, Kecamatan Kabila Bone, Kabupaten Bone Bolango - Hatu, Rauf A.; Ibrahim, Ridwan; Bumulo, Sahrain; Adahati, Fadjrin S. (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2024)
Community participation is highly needed in overseeing the management of village funds. This supervision is crucial to ensure that the use of village funds aligns with the needs of the community. This research aims to analyze community participation in the management of village funds in Biluango Village. The study employs a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The research is conducted in Biluango Village, Kabila Bone Subdistrict, Bone Bolango Regency. The findings indicate five models of community participation: First, the community provides ideas or suggestions according to the stage and idea gathering, starting from the bottom using a bottom-up approach; Second, community participation in the planning stage, where the community is involved in Village Deliberations to determine the priorities for village expenditures based on the assessment of community needs; Third, community participation in the implementation stage, where the community is directly involved in the programs implemented in the village; Fourth, participation in the monitoring stage, where the community actively participates in monitoring the implementation of development programs in the village; Fifth, community participation in the evaluation stage, where the community actively participates in the reporting and accountability processes of village fund management. Based on field findings, it can be concluded that the Biluango Village government provides space for the community in every stage of village fund management, from planning, implementation, monitoring, to evaluation stages.